Australian primary school communities' understandings of SunSmart: a qualitative study - Matthew Winslade; Bradley Wright; Dean Dudley; Wayne Cotton; Alexandra Brown (Elsevier, 2017)
Abstract Objectives: Skin cancer represents a major health issue for Australia. Childhood sun exposure is an important risk factor and evidence suggests the use of sun protection measures by Australian school children could be improved. This study examines how the SunSmart Program, a school‐based skin cancer prevention resource, can be supported to further increase sun protection behaviours to assist in lowering skin cancer incidence. Methods: The Health Promoting Schools (HPS) framework was adopted to select key stakeholders from a convenience sample of five school communities. Students, teaching staff and parents participated in semi‐structured focus group and individual interviews. A thematic analysis was used to extract key themes from the data. Results: Although these school communities were aware of sun protection practices and the risks associated with sun exposure, their understandings of the SunSmart Program were limited. Sun protection policy implementation was inconsistent and students were unlikely to engage in sun protection practices beyond the school setting. Conclusion and implications: School communities require additional support and engagement to holistically enforce the principles of the SunSmart Program.